2016
DOI: 10.5812/hepatmon.40357
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Hepatitis C Virus Genotypes in Middle Eastern Countries: A Systematic Review and Meta-Analysis

Abstract: ContextThe hepatitis C virus (HCV) is classified into seven genotypes and more than 100 subtypes. The treatment regimen, duration and efficacy of HCV therapy may vary according to the HCV genotype. Therefore, the HCV genotype should be determined prior to antiviral therapy. The objective of the current study was to review systematically all studies reporting the distribution of HCV genotypes in the countries that make up the Middle East.Evidence AcquisitionArticles were identified by searching electronic datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 145 publications
3
36
0
Order By: Relevance
“…12 The prevalence of genotype 1 over other genotypes in the current study was similar to reports from other Middle Eastern countries like the United Arab Emirates (UAE; 49.2%), Turkey (95.6%), Iran (56.2%) and Bahrain (37%). [18][19][20][21] However, other studies from Saudi Arabia, Yemen and Iraq found that genotype 4 was most frequent. [22][23][24] In the current study, alcohol and tobacco use were relatively uncommon.…”
Section: Discussionmentioning
confidence: 81%
“…12 The prevalence of genotype 1 over other genotypes in the current study was similar to reports from other Middle Eastern countries like the United Arab Emirates (UAE; 49.2%), Turkey (95.6%), Iran (56.2%) and Bahrain (37%). [18][19][20][21] However, other studies from Saudi Arabia, Yemen and Iraq found that genotype 4 was most frequent. [22][23][24] In the current study, alcohol and tobacco use were relatively uncommon.…”
Section: Discussionmentioning
confidence: 81%
“…Several recent studies have provided good evidence on genotype distribution and epidemiology of HCV in the Middle East region (57)(58)(59). However, determination of HCV seroprevalence rates among blood donors in the Middle East region could be helpful to develop prevention and control strategies more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Ghaderi-Zefrehi et al (2016) performed a systematic review and meta-analysis and announced that in Turkey (82%), Israel (68%), Cyprus (68%), and Iran (55%), genotype 1 was the most prevalent HCV genotype; moreover, HCV genotype 4 was the most prevalent genotype in the Middle East (74.7%), followed by genotype 1 (15.1%) (38). According to the literature, HCV genotype 4 is the most prevalent among chronic liver patients in Egypt and Saudi Arabia (2,38), while in a previous study in Iran, genotype 1a was the predominant genotype, followed by 3a and 1b (39); these findings were inconsistent with the current results. Furthermore, in a previous study, 1a genotype was the most frequent genotype (44.9%), followed by genotypes 3a (39.6%) and 1b (11.3%) (33,40); these results were contradictory with our findings.…”
Section: Discussionmentioning
confidence: 99%